Doing research with the Sociology of Knowledge Approach to Discourse - Keller, Reiner (Pandaemonium Germanicum, 2021)
This article introduces the sociology of knowledge approach to discourse (SKAD). This approach to social science discourse research has been widely received in the German-speaking world and for some time now also internationally. SKAD combines the analysis of power/knowledge regimes called for by Foucault with the interpretative paradigm of sociology, in particular with the pragmatist tradition of symbolic interactionism and the social constructivist sociology of knowledge. To this end, important basic concepts and, in particular, proposals for the methodology and implementation of corresponding discourse studies are presented.